Pengaruh Pengembangan Karir Dan Budaya Organisasi Terhadap Komitmen Organisasi Di Grand Rocky Hotel Bukittinggi - Rahmad Dani; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
The human resource base is key to determining the strength or resilience of an organization. In the business world, commitment to the organization is very important. Career and organizational culture negatively affect organizational commitment. The purpose of this study was to determine how the influence of organizational culture and career development on organizational commitment at Grand Rocky Hotel Bukittinggi. Quantitative and causal associative research examines cause-and-effect relationships. Validation and reliability assessments were conducted on ninety people using the saturated sampling method. A type of data analysis known as multiple linear regression analysis was used to investigate the effect of organizational culture and career development on employee commitment. The results showed that organizational commitment at Grand Rocky Hotel Bukittinggi is strongly influenced by career development and organizational culture.